Private Foundations' Giving for Development in 2013-2015 Ongoing efforts to better reflect private philanthropic giving in OECD-DAC statistics on development finance - Benn, Julia (OECD Development Co-operation Working Papers, 2018)
This working paper presents the results of the 2016-17 OECD data Survey on Global Private Philanthropy for Development and describes how this exercise relates to - and aims to complement - the existing regular data collection on development finance by the OECD Development Co-operation Directorate